Campus conspiracies: security and intelligence engagement with universities from Kent State to counter-terrorism. Issue 3 (3rd July 2019) - Gearon, Liam Francis
ABSTRACT: Security and intelligence agency concerns with universities range from the commissioning and protection of security-sensitive research, the ongoing recruitment of staff and students for covert security and intelligence work, as well as prominent counter-terrorist concerns. This is an ethically charged terrain of moral ambiguity which raises issues not only of academic freedom and freedom of speech but a less explored, cross-disciplinary complex of intelligence-led interactions from protection of campus property and personnel to ideological battles at the heart of the Academy itself. Current-day counterterrorism on campus agendas is, then, only an intensified aspect of an historical but ongoing and likely future interface between universities and security and intelligence agencies. Drawing on exemplars from the Kent State University shootings on 4 May 1970 at the height of the Vietnam War to the present era of globalised counter-terrorism, the article uses securitisation theory to conceptualise the historical, contemporary and future parameters of university engagements with the security and intelligence agencies as 'Incidental', 'Incendiary', and 'Inevitable'.